Sentiment Analysis of Long-Term Care Insurance in China Using NLP - Li, Yixuan (Transactions on Computer Science and Intelligent Systems Research, 2024)
Long-term care insurance (LTCI) is important for addressing the needs of aging populations and increasing long-term care demand. China initiated its LTCI pilot in 2016 and expanded it in 2019. This study employs Natural Language Processing (NLP) to analyze the sentiment impact of policyholders on LTCI decisions. By classifying sentiments in comments from various Chinese provinces, this study trained a Long Short-Term Memory (LSTM)-based deep learning model using annotated data and validated its accuracy with a pre-extracted test dataset. The application of the trained model to LTCI comments revealed sentiment distributions across different provinces, highlighting the developmental progress of LTCI since its pilot implementation. This research not only demonstrates the effective use of NLP in understanding sentiment trends but also underscores the significance of transitioning from qualitative to quantitative analysis. The study proposes integrating NLP with behavioral finance and insurance disciplines to enhance the utility and value of insurance products. This approach can guide product development, refine target marketing strategies, and inform policy decisions, contributing to the future expansion and success of LTCI in China.